MODAL SOSIAL PADA PEDAGANG PASAR PAGI ARENGKA KOTA PEKANBARU - Ginting, Lely Rosalina; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Trader is a person who resell goods to consumers directly or indirectly. An occupation as a trader is one of the informal sector jobs which is quite popular among the people nowadays amid the difficulty of getting a job. This research was conducted aiming to determine the characteristics of traders and forms of capital social traders in the Arengka Morning Market. The method used in this study is a qualitative researchs using purposing sampling technique with 7 person selected based on determined criteria. The theory used is the theory of capital social proposed by Fukuyama which consists of trust, social networks and social norms. To start a business not only requires financial principal but also strategies are needed to maintain their business through social capital. Based on results of research it was found that the social capital of trader in the Arengka Market was built because of an attitude of trust each other among traders that could make them simplify in borrowing goods each other, a social network that could help them because of cooperative relationship, and social norms that set traders behavior to be more directed so that make all together comfort and minimize disunity between one trader and another trader. Keywords : Traders, Social Capital